152 Understanding the lived experience of redeployed consultant physicians in the COVID-19 pandemic: essential information for leaders of future pandemics and emergencies. (16th November 2020) - Harrison, Beth; Robbins, Timothy; Randeva, Harpal; Patel, Kiran; Ray, Pijush
Abstract : A key challenge early in the COVID-19 pandemic was to identify staff able to meet the demand for senior medical assessment of an influx of acutely unwell respiratory patients. At UHCW we proposed that specialist physicians without recent general medicine experience could be safely and effectively redeployed to support the acute medical take. A rota of consultant physicians from 8 medical specialties, who did not participate in the acute medical take, was developed at pace to work alongside the medical registrar, in the segregated respiratory area of ED, following limited training. Two shifts were implemented within 6 days of inception, fitted around doctors' ongoing specialty roles. We gained feedback iteratively during the early phases. We then used a survey of all those asked to redeploy to explore their lived experiences and perceptions, with a 71% response rate. Median time since consultants had participated in an unselected medical take was 12 years. 66% were not GIM accredited. 84% found the online training useful. Many had concerns regarding availability of PPE and the risk of passing infection on to others, including their own vulnerable patients. 81% described concerns around personal competence. 63% of respondents felt this redeployment had made a positive difference to the COVID-19 response. However, 57% felt other groups should have been redeployed before them, and 45% reported they would not agree to be redeployed in a repeat scenario. Transparency regarding who was redeployed and equity amongst all physicians were the most important factors influencing decisions on future redeployment. We rapidly implemented a consultant redeployment programme during the pandemic, and redeployed doctors felt they made a positive difference. However, the same staff group may not willingly be redeployed during any future emergency. We hope this open and honest approach to collecting feedback will help to shape local and national planning for future major incidents